INNOVATIVE CONSUMERS OF THE DIGITAL AGE: OPINION SEEKING ON INSTAGRAM - AYAR, BAHADIR; AYDOĞAN, SİBEL (My University, 2019)
Nowadays the internet, social media, and mobile technologies are indispensable for our daily lives. During the past decade, online social networking sites such as Facebook, Twitter and their social media apps like Instagram have been caused profound changes in the communication and interaction of people. In addition, social networking sites have become the focus of interest for everyone who has access to the Internet and who can use computers, tablets or smartphones. Especially, youth and university students use the internet and social media as a mass communication vehicle with easy and fast access at an increasing frequency rate for their academic and/or other purposes. These tools are no longer just a good source of information but they have become a good reference guide for social interaction, games, information exchange and other purposes at the same time. People, -due to their nature- seek for entertainment, in order to have a good time and obtain information. Modern consumers use these social networking platforms as well to meet their needs to gather information on many subjects. This research aims to determine the effect of Instagram usage attitude on opinion seeking and the mediator effect of consumer innovativeness on this relationship. The results of this study reveal that consumers use Instagram as an information source about brands, products, and services. Moreover, Instagram usage attitude has a positive effect on opinion seeking.

Günümüzde internet, sosyal medya ve mobil teknolojiler günlük yaşantımızın vazgeçilmez bir parçası haline gelmiştir. Son on yılda, Facebook, Twitter gibi çevrimiçi sosyal ağ siteleri ve Instagram gibi sosyal medya uygulamaları insanların iletişiminde ve etkileşiminde derin değişikliklere neden olduğu söylenebilir. Ayrıca, sosyal ağ siteleri, internete erişimi olan ve bilgisayarları, tabletleri veya akıllı telefonları kullanabilen herkes için ilgi odağı haline gelmiştir. Özellikle genç bireyler ve üniversite öğrencileri, interneti ve sosyal medyayı kolay ve hızlı erişime sahip kitle iletişim aracı olarak akademik ve / veya diğer amaçları için artan bir sıklıkla kullanmaktadırlar. Bu araçların artık sadece iyi bir bilgi kaynağı değil, aynı zamanda sosyal etkileşim, eğlence, bilgi alışverişi ve diğer amaçlar için de iyi bir referans kaynağı haline geldiği söylenebilir. İnsanlar, doğaları gereği, iyi vakit geçirmek ve bilgi edinmek için eğlence arayışı içindedirler. Modern tüketiciler bu sosyal ağ platformlarını, birçok konuda bilgi toplamak için de kullanırlar. Bu çalışmada, Instagram kullanım tutumunun fikir arayışı üzerindeki etkisinin ve tüketici yenilikçiliğinin bu ilişki üzerindeki aracı etkisinin ortaya koyulması amaçlanmıştır. Elde edilen bulgular, tüketicilerin Instagram'ı markalar, ürünler ve hizmetler hakkında bir bilgi kaynağı olarak kullandıklarını ortaya koymaktadır. Dahası, Instagram kullanım tutumunun fikir arayışı üzerinde olumlu bir etkisi vardır.
DİJİTAL ÇAĞIN YENİLİKÇİ TÜKETİCİLERİ: INSTAGRAM'DA FİKİR ARAYIŞI
Keywords: İşletme Finans; İşletme